SEJARAH PERIODISASI KRITIK HADIS - Afandi, Eky Wifky (DIRAYAH : Jurnal Ilmu Hadis, 2023)
The large number of criticisms of the hadith by scholars and even shahabah does not mean doubting the authenticity of the hadith of the Prophet Muhammad, but seeing the limitations that are owned continue to the narrators of hadith as human beings who cannot be separated from mistakes both internal factors within humans themselves and externally outside humans. it is like other interests that encourage the occurrence of these mistakes. This research then seeks to describe the history of the periodization of hadith criticism by using a historical approach that has occurred since the time of the Prophet Muhammad to the present. Therefor this research is part of qualitative research. From this research, a result was obtained; First, that the history of the periodization of hadith criticism has been practiced since the Prophet's lifetime. Second, in fact, currently criticism of hadith is still being developed especially by orientalists. So in fact, periodization studies regarding the development of hadith criticism will continue.